This is considered an “easy” Q. Answer is 6, but I keep getting 7.

If f(x)=3x-1 and g(x)=4x+2, what is the value of g(f(0)+2)?

Considered easy by whom? Don’t let yourself get distracted by what other people say is easy. Your job is to know what you find hard, and to practice it until you build confidence.

Anyway, for nested function questions like this, I like to work from the inside out. Start with f(0).

    \begin{align*} f(x) &=3x-1\\ f(0)&=3(0)-1\\ f(0)&=-1 \end{align*}

Now here’s the tricky part. You’re asked for g(f(0)+2). That means you should evaluate f(0)+2 first. Since we know f(0)=-1, we know that f(0)+2=-1+2=1. Once you’ve got that, you can put it into the g function.

    \begin{align*} g(x)&=4x+2\\ g(1)&=4(1)+2\\ g(1)&=6 \end{align*}

Leave a Reply